The denial of native customary right over land in Sarawak - Loh, Ing Hoe; Kamaruddin, Hanim; Mustafa, Maizatun; Ibrahim, Irini; Abu Hanifah, Norha (2017)
Native Customary Rights (NCR) is not defined in the present Land Code (CAP. 81) 1958, Sarawak, (hereinafter referred to as the "Code") but Native Customary Land is. Section 2 of the Code defines Native Customary Land (NCL) to mean land in which native customary rights, whether communal or otherwise, have lawfully been created prior to the 1st day of January 1958 and still subsist as such. Although the law recognises NCR claim by customary tenure, the Government's definition and/or understanding of NCR claim is only restricted to cultivated area or farmed area locally referred to as "temuda" which must have been cultivated or farmed before 1st January 1958. On the other hand, the native believe that their NCR claim goes beyond their "temuda". It includes their communal lands or territorial domain locally referred to as "pemakai menua" and the "reserved virgin forests" within their "pemakai menua" locally refrred ti as "pulau". "Pulau" is preserved or reserved specifically to meet the domestic needs of the natives. Normally this is an area abundant with timber for boats, house, different kinds of fruit trees, jungle produce with medicinal value, a hunting ground, fishing ground etc to cater their daily needs. Purpose: To critically analyses the decide cases related to NCR cases in Sarawak and to compare with customary international law Design/Methodology?Approach: Qualitative methodology with historical and critical analysis approaches Finding: The recent decided case, Director of Forests Sarawak and anor v. TR Sandah ak Tabau & Ors by Federal Court has denied the native customary right on"pemakai menua" and "pulau". Therefore, a thorough study is needed to critically analyses and compares the judgment with customary international law.